IECEC 96. Proceedings of the 31st Intersociety Energy Conversion Engineering Conference
DOI: 10.1109/iecec.1996.553818
|View full text |Cite
|
Sign up to set email alerts
|

Zn-Sb alloys for thermoelectric power generation

Abstract: P-ZmSbs was recently identified as a new high performance p-type thermoelectric material (Caillat et al., 1996). A maximum dimensionless thermoelectric figure of merit of about 1.3 was obtained on p-type P-ZmSb3 samples at a temperature of about 400'C. This is the highest figure of merit ever obtained at this temperature for a p-type thermoelectric material. The possibility of improving ZT values by forming Zm,CdxSb3 solid solutions was studied. Preliminary results obtained on alloys between ZmSb3 and C&Sb3 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…[1][2][3][4] Theoretical studies on segmented legs 5,6 state that it is possible to increase the absolute efficiency from about 5% in commercially available materials to 18%. Various compounds are considered as materials for construction of segmented legs, with Bi 2 Te 3 , 5,7,8 skutterudites (e.g., CoSb 3 -based materials), 8,9 lead tellurides, 10,11 silicon-germanium alloys, 12,13 zinc antimonides, 14,15 and Te/Sb/Ge/Ag (TAGS) materials such as (AgSbTe) 0.15 (GeTe) 0.85 , 16,17 being only some of the most commonly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Theoretical studies on segmented legs 5,6 state that it is possible to increase the absolute efficiency from about 5% in commercially available materials to 18%. Various compounds are considered as materials for construction of segmented legs, with Bi 2 Te 3 , 5,7,8 skutterudites (e.g., CoSb 3 -based materials), 8,9 lead tellurides, 10,11 silicon-germanium alloys, 12,13 zinc antimonides, 14,15 and Te/Sb/Ge/Ag (TAGS) materials such as (AgSbTe) 0.15 (GeTe) 0.85 , 16,17 being only some of the most commonly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve its thermoelectric properties, a doping approach was used to optimize its carrier concentration and reduce its thermal conductivity. For instance, doping of Pb, Bi, Nb, Cu, Cd, Co, Sn, In, Al, Ga, Mg, Ge and Hg [7][8][9][10][11][12][13][14][15][16][17][18][19] have been investigated so far. The results showed that, however, only a small amount doping of one of these elements could lead to limited improvement of its thermoelectric performance.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the best solar cell is 3-5 times more efficient than thermoelectric devices [4]. Several implementations of TEGs focus on improving its efficiency by exploring advanced thermoelectric materials such as skutterudites [5,6], clathrates [7], Zn-Sb alloys [8], Pb-Te alloys [9][10][11], InGaN alloys [12], and ZnO alloys [13,14]. Higher efficiency TEGs have also been designed by using segmented thermoelectric legs to exploit the operating temperatures of several materials; thereby optimizing heat flow across the thermoelements [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%